Non-cereal and Legume Based Sourdough Metabolites - Aspri, Maria; Mustač, Nikolina Čukelj; Tsaltas, Dimitrios (My University, 2023)
In recent years, consumer demand for non-cereal grain-based products with high nutritional value and health-promoting properties has increased, and pseudocereals and legumes play an important role in the development of such products. As gluten-free ingredients, they have already shown the potential to increase the nutritional value of leavened baked goods, yet their use is limited due to technological disadvantages during the manufacturing process that can be overcome through sourdough fermentation. Wheat and rye are extensively studied for sourdough production, however, there is still much room for gaining knowledge on sourdoughs based on pseudocereals and legumes due to their high diversity. This chapter reviews the current knowledge and potential of pseudocereals and legumes as substrates for sourdough fermentation to improve the nutritional and health-related properties of these baked goods. Emphasis is placed on the influence of fermentation on reducing anti-nutritional factors, increasing protein digestibility, bioavailability of minerals, and functional value of phytochemicals, as well as on the production of dietary components, such as vitamins and other bioactive compounds.
Keywords: Non-cereal; Metabolites